INTENSE PHYSICAL EXERCISE AND ALCOHOL CONSUMPTION AS AN OXIDATIVE STRESS INDUCER: A REVIEW - Júnior, Zenon Ratzlaff; Fiorin, Pauline Brendler Goettems (Salão do Conhecimento, 2019)
Work developed at the Regional University of the Northwest of the State of Rio Grande do Sul (Unijuí);